2018
DOI: 10.1016/j.conctc.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of adaptations to multi-level intervention strategies to enhance implementation of clinical practice guidelines for treating tobacco use in dental care settings

Abstract: IntroductionOur team conducted a cluster randomized controlled trial (DUET) that compared the effectiveness of three theory-driven, implementation strategies on dental provider adherence to tobacco dependence treatment guidelines (TDT). In this paper we describe the process of adapting the implementation strategies to the local context of participating dental public health clinics in New York City.MethodsEighteen dental clinics were randomized to one of three study arms testing several implementation strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…A total of 45 separate CDSSs were reported in the 42 articles included as shown in Table 2 . The most commonly reported CDSSs were electronic prescribing or order sets (12/42, 29%) [ 65 , 69 , 70 , 75 , 76 , 79 - 81 , 83 , 88 , 94 , 98 ], followed by checklists, forms, or clinical guidelines (11/42, 26%) [ 63 , 66 , 73 , 82 , 89 , 92 , 93 , 95 , 102 , 104 ] and electronic alerts or reminders (9/42, 21%) [ 67 , 68 , 77 , 78 , 84 , 86 , 91 , 100 , 101 ]. Commonly, CDSSs were implemented in pharmacy or prescription services (17/42, 41%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 45 separate CDSSs were reported in the 42 articles included as shown in Table 2 . The most commonly reported CDSSs were electronic prescribing or order sets (12/42, 29%) [ 65 , 69 , 70 , 75 , 76 , 79 - 81 , 83 , 88 , 94 , 98 ], followed by checklists, forms, or clinical guidelines (11/42, 26%) [ 63 , 66 , 73 , 82 , 89 , 92 , 93 , 95 , 102 , 104 ] and electronic alerts or reminders (9/42, 21%) [ 67 , 68 , 77 , 78 , 84 , 86 , 91 , 100 , 101 ]. Commonly, CDSSs were implemented in pharmacy or prescription services (17/42, 41%).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies (24/42, 57%) reported the rationale for using a theory, model, or framework. The rationales reported included the formulation of knowledge or research questions [ 69 , 97 ]; addressing implementation factors leading to the use of CDSSs; and developing an implementation plan, including addressing modifications to an intervention [ 92 , 93 , 100 ]. Others cited the existing use or development of a theory, model, or framework [ 85 , 86 , 104 ] and the use of theory in aiding the scalability of intervention in different settings [ 74 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation